1988
DOI: 10.1126/science.240.4857.1319
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Manganese Reduction and Growth with Manganese Oxide as the Sole Electron Acceptor

Abstract: Microbes that couple growth to the reduction of manganese could play an important role in the biogeochemistry of certain anaerobic environments. Such a bacterium, Alteromonas putrefaciens MR-1, couples its growth to the reduction of manganese oxides only under anaerobic conditions. The characteristics of this reduction are consistent with a biological, and not an indirect chemical, reduction of manganese, which suggest that this bacterium uses manganic oxide as a terminal electron accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
979
1
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,246 publications
(998 citation statements)
references
References 21 publications
12
979
1
6
Order By: Relevance
“…It has been demonstrated that in cultures of Shewanella putrefaciens, iron oxide-surface contact was required for bacterial cells to mediate reduction of these metals (85). The rate of reaction depended on the type of oxide film under attack (69).…”
Section: Metal-reducing Bacteria (Mrb)mentioning
confidence: 99%
“…It has been demonstrated that in cultures of Shewanella putrefaciens, iron oxide-surface contact was required for bacterial cells to mediate reduction of these metals (85). The rate of reaction depended on the type of oxide film under attack (69).…”
Section: Metal-reducing Bacteria (Mrb)mentioning
confidence: 99%
“…The facultative bacterium Shewanella oneidensis MR-1, isolated from Oneida Lake 2 sediments (Myers and Nealson 1988), is able to use many organic carbon sources as electron 3 donors (e.g., lactate, pyruvate, propionate, acetate, formate, and serine) and can reduce a variety 4 of soluble or solid compounds, including iron III, manganese IV, nitrate, nitrite, thiosulfate, 5 trimethyl-amine N-oxide, thiosulfate, fumarate, uranium, and Cr(VI) (Scott and Nealson 1994;6 Venkateswaran et al 1999). Because of its metabolic versatility and its ability to reduce metals 7 to less mobile forms, this bacterium has been considered for use in bioremediation of subsurface 8 sites contaminated with metals and, as such, has been studied extensively over the last decade 9 the genome of S. oneidensis MR-1 was recently sequenced (Heidelberg et al 2002).…”
mentioning
confidence: 99%
“…Fe-reducing microorganisms are difficult to track in-situ because they belong to different phylogenetic lineages ) and they lack a unique molecular marker specific for Fe-reduction. Early investigations identified some microorganisms capable of reducing Fe oxides in pure culture studies (de Castro and Ehrlich 1970;Brock and Gustafson 1976;Lovley and Phillips 1988;Myers and Nealson 1988) including sulfur and sulfate reducing bacteria Roden et al 1993). Subsequent microbial diversity studies using primers targeting the 16S ribosomal RNA (rRNA) gene demonstrated that members of the gamma and delta-Proteobacteria, including known isolates, were often detected in a variety of Fe-rich environments including sediments (DiChristina and DeLong 1993; Coates et al 1996).…”
Section: Introductionmentioning
confidence: 99%